Gardens And Beyond Glass Painting (Little Rock, Arkansas Leisure Arts, Inc., 2001)
212 Designs.
Include Illustrations and Sketches.
Drawing Book.
Keywords: Drawing Book -- Drawing Book - Garden -- Drawing Book - Flowers